(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The functions of the heart and kidneys are closely interrelated. Their interaction can be defined as a complex biological relationships between distant organs, which are mediated through cellular, canlecular, nervous, endocrine and paracrineed factors. Under physiological conditions this connection.Helps maintain homeostasis and optimal functioning of the human body. Deterioration the function of one of these organs is caused by a vicious range of events leading to multi-organ failure accuracy. Although it is well known about the dysfunction renal function in patients with heart disease, it remains unclear whether renal dysfunction is passive response to cardiac failure activity. In clinical practice throughout the for more than 13 years, the term “cardiorenal syndrome" (CDS), i.e. coexistence cardiac and renal nature in the same patient.